Therapy of newly diagnosed follicular lymphoma - Westin, Jason R.; Neelapu, Sattva S. (Frontiers in Oncology, 2012)
Newly diagnosed follicular lymphoma is relatively common and can be effectively treated with several differing approaches. Although the disease is often considered incurable, it is highly responsive to therapy when indicated. This review discusses the indications for treatment, risk stratification systems, treatment options with supporting clinical trial data, and expected therapeutic outcomes in newly diagnosed follicular lymphoma.